Change, Modelization, and Algebra as a Language in the Costa Rican Mathematics Curriculum - Zumbado Castro, Marianela (2022)
The objective of this essay is to provide an analytical approach to those aspects in which the Ministry of Public Education of Costa Rica was consistent in relation to the organization of the Relations and Algebra area of the mathematics teaching curriculum from the III cycle of Education General Basic to Diversified Education. To argue the answer, the OECD perspective is used for the category “Change and relationships,” and it is compared critically with the general skills of the area of Relationships and Algebra of the Costa Rican mathematics programs, through a methodological design of qualitative approach that uses documentary-interpretive analysis. Three groups of skills were identified as analytical references: change, modeling, and algebra as a language. It is stated that the ministerial proposal is consistent with the OECD and is maintained until Diversified Education. In addition, it is argued that problem posing skills require research for their proper implementation in the classroom.